k = 2 ∑ 2 0 1 6 ∣ ∣ ∣ k 2 0 1 6 i ∣ ∣ ∣ + ∣ ∣ ∣ ∣ ∣ ∣ k = 2 ∏ 2 0 1 6 k 2 0 1 6 i ∣ ∣ ∣ ∣ ∣ ∣ = ?
Notations :
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The last 2 summation signs, shouldn't they be product signs instead? It does not change the result.
S = k = 2 ∑ 2 0 1 6 ∣ ∣ k 2 0 1 6 i ∣ ∣ + ∣ ∣ ∣ ∣ ∣ k = 2 ∏ 2 0 1 6 k 2 0 1 6 i ∣ ∣ ∣ ∣ ∣ = k = 2 ∑ 2 0 1 6 ∣ ∣ ∣ e 2 0 1 6 ( ln k ) i ∣ ∣ ∣ + ∣ ∣ ∣ ∣ ∣ k = 2 ∏ 2 0 1 6 e 2 0 1 6 ( ln k ) i ∣ ∣ ∣ ∣ ∣ = k = 2 ∑ 2 0 1 6 ∣ cos θ k + i sin θ k ∣ + ∣ ∣ ∣ ∣ ∣ exp ( i k = 2 ∑ 2 0 1 6 θ k ) ∣ ∣ ∣ ∣ ∣ = k = 2 ∑ 2 0 1 6 1 + ∣ ∣ e Θ i ∣ ∣ = 2 0 1 5 + ∣ cos Θ + i sin Θ ∣ = 2 0 1 5 + 1 = 2 0 1 6 Let θ k = 2 0 1 6 ( ln k ) Let k = 2 ∑ 2 0 1 6 θ k = Θ Note that ∣ cos θ k + i sin θ k ∣ = 1
Problem Loading...
Note Loading...
Set Loading...
∣ k 2 0 1 6 i ∣ = ∣ e 2 0 1 6 ( ln k ) i ∣ = 1
So the summation is simply k = 2 ∑ 2 0 1 6 ( 1 ) = 2 0 1 5 .
Now the product is:
∣ ∣ ∣ ∣ ∣ k = 2 ∏ 2 0 1 6 k 2 0 1 6 i ∣ ∣ ∣ ∣ ∣ = ∣ ∣ ∣ ∣ ∣ ∣ ( k = 1 ∏ 2 0 1 6 k ) 2 0 1 6 i ∣ ∣ ∣ ∣ ∣ ∣ = e 2 0 1 6 ln ( k = 1 ∏ 2 0 1 6 k ) i = 1
Note:- Since ∣ ∣ ∣ e i θ ∣ ∣ ∣ = 1 .
Hence the sum expression is simply 2 0 1 5 while product expression is 1 . Hence answer is 2 0 1 5 + 1 = 2 0 1 6 .